2021
DOI: 10.3201/eid2711.204893
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Divergent Highly Pathogenic Avian Influenza A(H5N8) Viruses in Wild Birds, Eastern China

Abstract: H ighly pathogenic avian infl uenza (HPAI) A(H5Nx) clade 2.3.4.4 viruses, which originated from the HPAI A(H5N1) clade 2.3.4 of the A/ Goose/Guangdong/1/96-lineage in China, have spread globally, causing severe disease in poultry and wild birds (1-4). According to the World Health Organization, clade 2.3.4.4 viruses have evolved into 8 subclades, designated as clades 2.3.4.4a-h (https://www.who.int/influenza/vaccines/virus/202002_zoonotic_vaccinevirusupdate.pdf). In 2013, a novel reassortant A(H5N8) clade 2.3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…H5N8 viruses have been circulating in wild birds since 2014, and are responsible for numerous disease outbreaks in domestic poultry in many countries in Asia, Europe, Africa, and North America (Abolnik et al, 2019;Baek et al, 2021;El-Shesheny et al, 2021;Lee et al, 2015;Napp et al, 2018); however, even though different H5N8 strains have been detected in wild birds and occasionally in ducks or geese in past years, they have not become established in domestic waterfowls and spread or have caused problems in chickens in China. In this study and the studies reported by others (He et al, 2021;Li et al, 2021;Xiong et al, 2021), H5N8 viruses were detected in over 17 different species of wild birds over just a few months. Since it is impossible to prevent wild birds from being infected with the virus, the H5N8 virus may have a high probability of circulation in wild birds in China.…”
Section: Discussionsupporting
confidence: 76%
“…H5N8 viruses have been circulating in wild birds since 2014, and are responsible for numerous disease outbreaks in domestic poultry in many countries in Asia, Europe, Africa, and North America (Abolnik et al, 2019;Baek et al, 2021;El-Shesheny et al, 2021;Lee et al, 2015;Napp et al, 2018); however, even though different H5N8 strains have been detected in wild birds and occasionally in ducks or geese in past years, they have not become established in domestic waterfowls and spread or have caused problems in chickens in China. In this study and the studies reported by others (He et al, 2021;Li et al, 2021;Xiong et al, 2021), H5N8 viruses were detected in over 17 different species of wild birds over just a few months. Since it is impossible to prevent wild birds from being infected with the virus, the H5N8 virus may have a high probability of circulation in wild birds in China.…”
Section: Discussionsupporting
confidence: 76%
“…Widely circulated wild-bird AIVs can be introduced into domestic poultry by migratory birds and domestic waterfowl, thereby increasing the risk of cross-species transmission between birds and mammals. The H5N8 viruses continually circulate in migratory birds in Asia, Europe, North America, and Africa and are highly likely to generate novel mutants by reassortment with other subtypes ( 52 54 ). Currently, the H10 viruses are divided into Eurasian and North American lineages and are widely circulating in both wild migratory birds and domestic poultry ( 32 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Maximum-likelihood (ML) phylogenies of the H5 gene, 2020-H5N8 (n = 40) and SX116-H5N2 were both classified in 2.3.4.4b, and were further diverged into two phylogenetically distinct sub-clades: 2.3.4.4b1 and 2.3.4.4b2 ( Figure 1 ) [ 7 , 32 , 33 ]. The high bootstrap value also supported the two novel sub-clades.…”
Section: Resultsmentioning
confidence: 99%